2021
DOI: 10.21203/rs.3.rs-490884/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of medical students towards COVID19 in Sudan, 2020: A cross sectional study among 19 universities

Abstract: Introduction: Since December 2019, an outbreak of severe respiratory infection (COVID-19) emerged in the city of Wuhan in China. It quickly spread around the world and is now a pandemic of epic proportions. Medical students are the future generation of doctors who will have to face this and any future similar catastrophe. The knowledge, awareness and practice of medical students toward Covid19 pandemic is of most importance as it demonstrates their preparedness to deal with this pandemic.Objective: To assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…[11] revealed that 83.7 % and 92.2% of early years and final years students respectively correctly knew the asymptomatic nature of the disease. A cross-sectional study from Sudan [17], reported that only 27.7% knew the main combination of clinical symptoms of the disease. While [18], an Indian study, explained that only 39.7% of students knew the asymptomatic nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] revealed that 83.7 % and 92.2% of early years and final years students respectively correctly knew the asymptomatic nature of the disease. A cross-sectional study from Sudan [17], reported that only 27.7% knew the main combination of clinical symptoms of the disease. While [18], an Indian study, explained that only 39.7% of students knew the asymptomatic nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…[13], [33] stated that 91.0% and 98.7% of students respectively wear N95 masks frequently. Also, a study from Sudan showed that 72.6% of medical students identified that wearing masks during work in the hospital protects against the spread of the virus [17]. While [18] clarified that 73.15 % of students thought that wearing a surgical mask can protect people from COVID-19.…”
Section: Discussionmentioning
confidence: 99%